Foraging Ecology and Diurnal Activity Patterns of Klipspringer (Oreotragus oreotragus) in Yetefet Woyenat Forest, East Gojjam, Ethiopia - Melaku Bireda; Mesele Yihune (International Journal of Zoology)
The foraging ecology and diurnal activity patterns of the klipspringer (Oreotragus oreotragus) were studied in Yetefet Woyenat Forest from September 2017 to August 2018 during the dry and wet seasons. Data were collected by visual observation using focal and scan sampling methods. The result indicated that klipspringers were observed feeding on grasses, herbs, trees, and shrubs, but were primarily browsers during both wet and dry seasons. Carissa edulis was the most consumed plant species in the study area, followed by Rosa abyssinica and Maytenus arbutifolia. Despite moderate ambient temperatures, klipspringers were mostly active during early morning and late afternoon, feeding 45.56% of the daylight hours during the dry season and 43.75% during the wet season. Klipspringers were facing threats due to human activities in the study area. Thus, appropriate conservation measures should be taken to reduce disturbance of their ecology.